Pelatihan Keterampilan Menjahit Celana Santai Bagi Masyarakat Kecamatan Muaragembong, Kabupaten Bekasi - Suryawati Suryawati; Sri Listiani (IKRA-ITH ABDIMAS, 2023)
One of the Higher Education Tri Dharma activities that must be carried out is Community Service activities. Community Service this time, the State University of Jakarta, especially the Faculty of Engineering, plays a role in carrying out Community Service Activities (PkM), namely in Muaragembong District, Bekasi Regency as a fostered area of the Faculty of Engineering UNJ. One of the goals of PKM activities is learning and community empowerment to support alternative solutions in meeting the needs of the target community independently and sustainably. The implementation method used in the implementation of PKM activities is the first step of collecting data on the target audience, surveying the location, preparing for implementation and then carrying out activities.The results of the PKM activity are expected to increase the knowledge and skills of the residents of the simple coastal village of Muaragembong in sewing casual pants, which can be applied in entrepreneurship in the fashion sector to improve the family economy